Mejorando el acceso a la atención del aborto terapéutico en el Instituto Nacional Materno Perinatal en salvaguarda del derecho a la vida y la salud de la mujer - Chapa-Romero, Jacqueline (2021)
Objective: Describe the actions carried out by the National Maternal Perinatal Institute, regarding access to health services for the care of women for therapeutic abortion. Material and Methods: Descriptive, cross-sectional study. All the files of requests for therapeutic abortion that were attended at the National Maternal-Perinatal Institute during the periods from January to December 2019 and 2020 were reviewed. Results: 117 and 59 requests for therapeutic abortion were attended during the 2019 and 2020 periods respectively. Age is not an impediment to request the procedure of voluntary therapeutic interruption of pregnancy, only in the cases of minors, the signature of the minor's parents or guardians is accompanied. In addition, the institution complies with informing the Public Ministry to guarantee the legal measures of judicial protection in defense of the sexual freedom of the minor. All applications have followed the administrative procedure for evaluation by the medical board, in which the acceptance or denial of the procedure is determined. In 2019 and 2020, 105 and 55 applications were approved by the medical board, respectively; and denied 12 and 4 cases respectively. They met the criteria of the MINSA national guidelines in 90 and 46 requests during the years 2019 and 2020 respectively; remaining within the scope of the institutional medical protocol in 27 and 13 cases respectively. They have a mental health report accepted by the medical board in 105 and 55 cases during the 2019 and 2020 periods respectively. Conclusion: All the requests for voluntary therapeutic interruption of pregnancy, presented by the pregnant women, have followed the administrative procedure for their evaluation by a medical board, however, in some files, no copy of the mental health report has been found.